2018
DOI: 10.5455/medscience.2018.07.8780
|View full text |Cite
|
Sign up to set email alerts
|

The use of serum hypoxia-inducible factor two alpha levels and diagnostic values in adult carbon monoxide poisoning

Abstract: Carbon monoxide poisoning (COP) is a life-threatening intoxication which should be interfered immediately to be prevented from serious damages. The effect of carbon monoxide (CO) in the body at the cell level is mediated by a CO-releasing molecule. This molecule results in heme degradation via heme oxygenase. Because of the high affinity of CO on heme, many enzymes with biological signal transduction cause heme protein increase. Universally, this signal activation with similar enzymes and mechanisms are used i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…[20] In the study of Altıntop et al, headache(46.4%) was the most prevalent complaint, followed by nausea with vomiting(42.9%), asthenia and weakness(41.1%). [3] In this study, the most prevalent complaintwas nausea, and headache and dizziness were the other common complaints.…”
Section: Discussionmentioning
confidence: 65%
See 4 more Smart Citations
“…[20] In the study of Altıntop et al, headache(46.4%) was the most prevalent complaint, followed by nausea with vomiting(42.9%), asthenia and weakness(41.1%). [3] In this study, the most prevalent complaintwas nausea, and headache and dizziness were the other common complaints.…”
Section: Discussionmentioning
confidence: 65%
“…In our country, the usage of stoves, barbecues and water heaters is the most important cause of COP. [3] The literature has shown that poisonings due to stoves are the most common cause of poisoning. [3,4,19] The results of our study supported the literature.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations